Utilization of polarization SAR Data for mapping coastal zone vegetation - Marghany, Maged; Zabidi, Noradilawati; Wan Kadir, Wan Hazli; Hashim, Mazlan (2006)
Coastal vegetation is one of the important natural ecosystems that act as protection from sea wave erosion phenomena and supply oxygen to the surrounding organisms. POLSAR data with multi-band and multi-polarization is selected for these studies which are acquired on September 19, 2000 for coastal vegetation mapping. Two methods are performed to CVV, LHH and LHV bands: polarization signature analysis and comparison of classification between two clustering techniques (Fuzzy-k-mean and ISODATA). The result shows that L band with HV polarization can distinguish coastal vegetation better than CVV. Furthermore, classification results of LHH and LHV shows that the Fuzzy-k-mean clustering is provided accuracy of 76% and also with kappa statistic of 70%.